Reflecting self : an exploration of drawing trace as reciprocity between self and life-world, with reference to my own drawing and selected works of Diane Victor - Kruger, Marieke; Malan, Marieke (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.